BETUMBANG APAM TRADITION AS A MEDIUM OF ISLAMIC EDUCATION: : CLIFFORD GEERTZ'S INTERPRETATIVE ANALYSIS OF RELIGIOUS VALUES - Fadil, Muhammad Ikhsan; Jamalie, Zulfa; Nor, Asikin (UIN Antasari Banjarmasin, 2024)
The era of modernization has presented various challenges and significant changes in every aspect of life, including education. In the context of these changes, tradition still plays an important role as a medium for conveying religious values in society. This study employs a qualitative methodology with an ethnographic approach, utilizing Clifford Geertz's interpretative framework for analysis. This research aims to analyze the Betumbang Apam tradition as a medium of Islamic education in understanding and strengthening the religious values of the community at the Palajau Sacred Mosque. The results of this study show that the Betumbang Apam tradition is a reflection of cultural wealth and a strong medium in conveying religious values. This tradition reflects faith values, such as belief in Allah, gratitude and early introduction to the mosque to children; moral values, such as respect for scholars and parents; and social values, such as togetherness and friendship. In the context of modernization, this tradition remains relevant because it strengthens people's religious understanding through deep symbolism. The results of this study reinforce Clifford Geertz's “thick description” theory, showing that the Betumbang Apam tradition has layers of meaning that enrich spiritual and social understanding in the Muslim community in Palajau.